Rhétorique de la futurité : scénarios, design fiction, prototypes et autres modalités évaporées de la science-fiction - Paul Graham Raven (ReS Futurae)
This essay proposes that science fiction is actually a subgenre of a far larger, medium agnostic genre of stories that portray imagined futures, and that by looking at the choices and strategies used during the production of these stories, we can get an insight into the way they frame the future they present. The framework is based in a 2x2 matrix in which two continua of narrative stragegy are entangled : the first dichotomy is that between the diegetic and mimetic modes, and the second is that between the dramatic and spectacular logics. By positioning a given text on this typological map, it becomes possible to broadly predict the rhetorical frame in which that narrative’s future is presented.